2021
DOI: 10.1161/circheartfailure.120.008076
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Sex Differences in Physical Frailty Phenotypes in Heart Failure

Abstract: Background: Although women with heart failure (HF) are potentially more likely to be physically frail compared with men with HF, the underlying contributors to this sex difference are poorly understood. The purpose of this study was to characterize sex differences in physical frailty phenotypes in HF. Methods: We prospectively enrolled adults with class I–IV HF. Physical frailty was measured with the frailty phenotype criteria. Symptoms of dyspnea, slee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 52 publications
0
32
0
Order By: Relevance
“…We thank Martin et al for their interest in our recent publication on characterizing sex differences in physical frailty in heart failure (HF). 1 We appreciate their insight and suggestions, and we are glad to respond to the key points raised in their letter and continue the dialogue on this important topic.…”
Section: In Responsementioning
confidence: 92%
“…We thank Martin et al for their interest in our recent publication on characterizing sex differences in physical frailty in heart failure (HF). 1 We appreciate their insight and suggestions, and we are glad to respond to the key points raised in their letter and continue the dialogue on this important topic.…”
Section: In Responsementioning
confidence: 92%
“…Authors found that women with HF were significantly more likely to be physically frail than men. Frailty was related with higher overall comorbidity burden in both men and women although frail women had a worse symptom profile ( 24 ). However, such population was significantly younger than that in our study (mean age 63.6 vs. 81.4 years) and had different baseline characteristics: 71% had reduced LVEF and almost 50% had NYHA III-IV functional status (which may, in part, explain the discrepant findings).…”
Section: Discussionmentioning
confidence: 99%
“…Frailty and cachexia, common features of AHF ( 4 , 24 ), are more frequently seen in women ( 24 ). Physical frailty is characterized by worse symptom characteristics in women, and worse body composition characteristics in men ( 25 ). However, current frailty assessment tools are not sex-specific, and future research is needed to identify the ideal index for frailty assessment in women, and sex differences in reversibility of frailty with HF therapies ( 25 ).…”
Section: Clinical Presentation Of Advanced Heart Failure In Womenmentioning
confidence: 99%
“…Physical frailty is characterized by worse symptom characteristics in women, and worse body composition characteristics in men ( 25 ). However, current frailty assessment tools are not sex-specific, and future research is needed to identify the ideal index for frailty assessment in women, and sex differences in reversibility of frailty with HF therapies ( 25 ). Women are also admitted less frequently than men for acute decompensated HF ( 1 ) which may lead to delayed recognition of advanced disease.…”
Section: Clinical Presentation Of Advanced Heart Failure In Womenmentioning
confidence: 99%